The environment profession in Australia: a status report. Issue 1 (2nd January 2019) - Thomas, Ian
ABSTRACT: The environment profession in Australia is well established, and past conjecture about its future has been positive. As with other professions, and areas of the economy generally, future employment will be influenced by pressures from automation and globalization. Building on earlier surveys of the environment profession, this article presents results of a recent survey to provide information about the characteristics of those in the profession, their thoughts about their professional futures, and the skills that are important in their professional lives. The results indicate a maturing profession, generally with little difference from the earlier surveys, However, while most continue to be positive about their place in the profession, there are signs of shifts in the focus of some of the professional's work, and their concern about the general support for the profession in the future. Importantly the skills identified as important for the respondents to carry out their environment roles are compatible with skills considered to be critical for future contributions to the economy and society. This suggests environment professionals could take opportunities to promote the profession, and the range of contributions that the individuals can make in the future.